2020
DOI: 10.1101/2020.09.05.284240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The allelic rice immune receptor Pikh confers extended resistance to strains of the blast fungus through a single polymorphism in the effector binding interface

Abstract: Arms race co-evolution drives rapid adaptive changes in pathogens and in the immune systems of their hosts. Plant intracellular NLR immune receptors detect effectors delivered by pathogens to promote susceptibility, activating an immune response that halts colonization. As a consequence, pathogen effectors evolve to escape immune recognition and are highly variable. In turn, NLR receptors are one of the most diverse protein families in plants, and this variability underpins differential recognition of effector… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 79 publications
(160 reference statements)
0
40
0
Order By: Relevance
“…This NLR pair was initially cloned from Tsuyuake rice (Ashikawa et al, 2008), and has since been shown to occur in allelic variants, which include Pikp, Pikm, Piks, Pikh, and Pik* (Costanzo and Jia, 2010;Jia et al, 2009;Wang et al, 2009;Zhai et al, 2011). Remarkably, the integrated HMA domain is the most sequence-diverse region among Pik-1 variants, consistent with the view that the receptor is under selection imposed by AVR-Pik (Białas et al, 2018;Costanzo and Jia, 2010;De la Concepcion et al, 2020;Zhai et al, 2014). Conversely, AVR-Pik alleles carry only five amino acid replacements, all of which map to regions located at the HMA-binding interface, indicating the adaptive nature of those polymorphisms (Longya et al, 2019).…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…This NLR pair was initially cloned from Tsuyuake rice (Ashikawa et al, 2008), and has since been shown to occur in allelic variants, which include Pikp, Pikm, Piks, Pikh, and Pik* (Costanzo and Jia, 2010;Jia et al, 2009;Wang et al, 2009;Zhai et al, 2011). Remarkably, the integrated HMA domain is the most sequence-diverse region among Pik-1 variants, consistent with the view that the receptor is under selection imposed by AVR-Pik (Białas et al, 2018;Costanzo and Jia, 2010;De la Concepcion et al, 2020;Zhai et al, 2014). Conversely, AVR-Pik alleles carry only five amino acid replacements, all of which map to regions located at the HMA-binding interface, indicating the adaptive nature of those polymorphisms (Longya et al, 2019).…”
Section: Introductionmentioning
confidence: 57%
“…figure 33A) (De la Concepcion et al, 2018;Maqbool et al, 2015). We note that the MKANK/EMVKE and IAQVV/LVKIE regions map to two of the three interaction interfaces previously described to underpin binding of AVR-PikD, and other AVR-Pik variants, to Pik-HMAs (De la Concepcion et al, 2020, 2019.…”
Section: Pikp-1 and Pikm-1 Nlr Receptors Convergently Evolved Throughmentioning
confidence: 63%
See 3 more Smart Citations